Necrotic Lymphadenopathy in a 12-year-old Boy with Enteric Fever: An Uncommon Presentation - Ravi Chirag; Bharath Jayachandra; Thirunavukkarasu Arun Babu (Pediatric Infectious Disease)
This case report describes a 12-year-old boy who presented with high-grade fever, joint pain, abdominal pain, and general weakness. The Widal test showed positive results with ‘O’ and ‘H’ antibody titers of 1:320. Additionally, the blood culture report confirmed the growth of Salmonella typhi, leading to the diagnosis of enteric fever. An abdominal ultrasound (USG) was performed due to severe abdominal pain, revealing the presence of multiple discrete necrotic lymph nodes in the right subhepatic and right iliac fossa, with the largest node measuring 1.6 cm. The child was treated with ceftriaxone (1 gm twice daily) and azithromycin (20 mg/kg), resulting in a gradual improvement of symptoms. To the best of our knowledge, this is the first reported case of necrotic lymphadenopathy in enteric fever confirmed by abdominal imaging in the pediatric population.